Die öffentliche Risikovorsorge im Agrarrecht Ein Grundprinzip - Poppe, Anna-Lena (Schriften zum Agrar-, Umwelt- und Verbraucherschutzrecht, 2023)
The work contains a legal doctrinal justification of public risk management as a fundamental principle of agricultural law. It provides a valuable contribution to the development of legal dogmatics, methodology and system building in agricultural law by analysing and systematising the public risk management measures in non-constitutional agricultural law and by examining public risk management in agriculture from a constitutional and Union law perspective. Furthermore the work examines the legislative status quo and offers concrete implementation recommendations for an improved legislative framework.